Spillover Effect of Official Development Assistance on Sectoral Economic Growth in West African Economic and Monetary Union Countries - Sessinou Erick Abel Dedehouanou; Abou Kane (International Journal of Economics and Financial Issues, 2021)
For decades, the literature on the relationship between official development assistance (ODA) and economic growth is characterized by ambiguity. This study removes such ambiguity for West African Economic and Monetary Union (WAEMU) countries by considering gross domestic product (GDP) according to the production perspective and paying attention to spatial spillover effects. The results obtained by system generalized method of moments for the period 2000–2018 showed a link between economic growth and ODA, which manifests itself through a positive and significant impact of the latter on the value added in the secondary and tertiary sectors. In addition, the value added in the secondary sector of a WAEMU country depends positively on the aid provided to other WAEMU countries that are geographically close to that country or located on the same road corridor. Our results inform donors for an efficient allocation of development aid in the Union.